Atezolizumab Plus Bevacizumab-induced Recalcitrant Pyoderma Gangrenosum Treated with Baricitinib: A Case Report - Han Seul Kim; Ji Eun Kwon; Young Joon Park (Acta Dermato-Venereologica, 2023)
Abstract is missing (Short communication)